1997
DOI: 10.1128/jb.179.17.5347-5354.1997
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical basis for glucose-induced inhibition of malolactic fermentation in Leuconostoc oenos

Abstract: The sugar-induced inhibition of malolactic fermentation in cell suspensions of Leuconostoc oenos, recently reclassified as Oenococcus oeni (L. M. T. Dicks, F. Dellaglio, and M. D. Collins, Int. J. Syst. Bacteriol. 45:395-397, 1995) was investigated by in vivo and in vitro nuclear magnetic resonance (NMR) spectroscopy and manometric techniques. At 2 mM, glucose inhibited malolactic fermentation by 50%, and at 5 mM or higher it caused a maximum inhibitory effect of ca. 70%. Galactose, trehalose, maltose, and man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…MLF is regulated by glucose. As little as 2 mM glucose inhibits MLF by 50% (Miranda et al, 1997). Similar results were recorded in the presence of galactose, trehalose, and maltose.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…MLF is regulated by glucose. As little as 2 mM glucose inhibits MLF by 50% (Miranda et al, 1997). Similar results were recorded in the presence of galactose, trehalose, and maltose.…”
supporting
confidence: 73%
“…Similar results were recorded in the presence of galactose, trehalose, and maltose. Ribose and 2-deoxyglucose, however, had no effect on the conversion of L-malic acid (Miranda et al, 1997). Glucose inhibition is reversed by the addition of fructose or citrate, which leads to an increase in intracellular concentrations of glucose-6-phosphate, 6-phosphogluconate, and glycerol-3-phosphate (Miranda et al, 1997).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…ND, not detected; MDH, metal-dependent hydrolase; GR, glutathione reductase; GPDH, glyceraldehyde-3-phosphate dehydrogenase; IMPDH, inosine-5Ј-monophosphate dehydrogenase; HPr, phosphocarrier protein. (30). Moreover, phosphomethylpyrimidine (HMP-P) kinase, which catalyzes the stepwise phosphorylation of HMP-P into HMP-PP (21), a heterocyclic intermediate in the de novo synthesis of thiamine diphosphate (ThDP), was increased in ethanol-adapted cells.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by the fact that cF leakage followed the global trend of ethanol concentration dependence that paralleled the increase in passive proton influx rates at increasing ethanol concentrations. NAD ϩ is an important cofactor of the malolactic enzyme, and it has been reported that the delicate balance between NAD ϩ and NADH affects the activity of the enzyme (28). Conceivably, nonspecific leakage of intracellular material will significantly disturb this balance, and consequently it is expected that cell metabolism will be negatively affected.…”
Section: Discussionmentioning
confidence: 99%